A Methodological Exploration for Estimating Economic Effectiveness of Economic Infrastructure - Gwang-Nam Rim; Chol-Ju An (Modern Perspectives in Economics, Business and Management Vol. 1, 2021)
Economic Infrastructure is a prerequisite for economic development. To this end, it is necessary to reveal the theoretical background for estimating the effectiveness of economic infrastructure and establish the methodology for estimating the effectiveness. Until now, there have been a number of qualitative and quantitative studies that investigate the effect of infrastructure on the economy. However, it can hardly say that there is an agreed upon methodology for estimating such effectiveness. The aim of this article is to solve methodological problems arising in estimating the effectiveness of infrastructure in terms of economic, physical-value, and spatio-temporal aspects. The first section of the paper discusses theoretical problems for estimating the effectiveness of economic infrastructure. For this, authors analyze the preceding studies on economic infrastructure as an economic concept and on this basis, systemize its specific features and roles in a new way. The second section illustrates the main indicators and methodology for estimating the effectiveness of economic infrastructure. In this section, authors apply various indicators related to physical and value aspects to suggest the methodology for estimating the space-time effectiveness of economic infrastructure. The findings are that the contribution of economic infrastructure to economy is interrelated with its economic effectiveness, but economic contents of these concepts are not same and therefore, it is reasonable to estimate its economic effectiveness using benefit to cost approach rather than functional approach. This study can be of significance in decision-making related to infrastructural investment for policymakers or investors.